2017
DOI: 10.1248/bpb.b17-00340
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Benefit Feeling Rate Based on the Sho of OTC Kakkonto, Cold Remedy and Cold Remedy with Kakkonto Combination Product

Abstract: Kakkonto (KK), a traditional Japanese Kampo formulation for cold and flu, is generally sold as an OTC pharmaceuticals used for self-medication. Kampo formulations should be used according to the Shosymptoms of Kampo medicine. These symptoms refer to the subjective symptoms themselves. Although with OTC pharmaceuticals, this is often not the case. We surveyed the relationship of agreement of Sho with the benefit feeling rate (BFR) of patients who took KK (n 555), cold remedies with KK (CK, n 315), and general c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…During inspection of questionnaire responses, questionnaires with the same response selected for Q1 through Q12 were defined as insincere responses and excluded from analysis. 19 Data were extracted from patient questionnaire response results according to the flow shown in Supplemental Figure S3(a). Only respondents who regularly visit community pharmacies were the target of this study, and respondents, who irregularly submit prescriptions (for colds and other acute diseases) and insincere respondents, were excluded from analysis.…”
Section: Resultsmentioning
confidence: 99%
“…During inspection of questionnaire responses, questionnaires with the same response selected for Q1 through Q12 were defined as insincere responses and excluded from analysis. 19 Data were extracted from patient questionnaire response results according to the flow shown in Supplemental Figure S3(a). Only respondents who regularly visit community pharmacies were the target of this study, and respondents, who irregularly submit prescriptions (for colds and other acute diseases) and insincere respondents, were excluded from analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Amitriptyline has been used for various pain syndromes including fibromyalgia . Kakkonto can be used for stiff shoulders . Keishikaryukotsuboreito has been used for anxiety disorder, functional palpitation, dizziness, and various other symptoms associated with anxiety .…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the abdominal examination is unique to Japan, and considered to be one of the most important approaches ( 6 ). Several studies have reported that the most suitable formula is chosen for a patient after determining Sho as a Kampo concept ( 3 , 5 , 7 , 8 ). For example, Okita et al ( 8 ) described their observations from a clinical trial that involved selected patients who met the criteria of Kakkonto- Sho , and demonstrated that it is more effective than conventional remedies.…”
Section: Introductionmentioning
confidence: 99%